Effects of Sertraline on Spermatogenesis of Male Rats and its Reversibility after Terminating the Drug - Ghorbani, Hamidreza; Akhavanrezayat, Alireza; Jarahi, Lida; Memar, Bahram; Amouian, Sakineh; Attaranzadeh, Armin; Ebrahimi, Sadegh (Urology Journal, 2021)
Purpose: The purpose of this research was to studding the effects of Sertraline on spermatogenesis of male rats and whether these probable effects are constant or provisional after terminating the drug. Materials and Methods: In this study, 32 two-month old male Wistar albino rats were equally divided into the Sertraline-treated and the control groups. The drug group was gavaged with Sertraline daily while the control group was gavaged with water at the same volume. After 80 days, half of the rats in each group were selected randomly for hormonal evaluations and bilateral orchiectomy. Histological and hormonal evaluations were performed. The remaining half of rats were kept alive for 90 more days without intervention and then underwent hormonal evaluation and bilateral orchiectomy in a similar fashion. Results: There was no difference between the testes histology and pathology of the sertraline-treated and the control groups. There was a significant decrease in serum FSH in the Sertraline-treated group compared to the control group (P <0.05). However, this decline appeared to be reversible following termination of exposure to Sertraline. FSH returned to pretreatment levels in the remaining treated rats following 90 days of treatment cessation. Conclusion: Within the time-frame studied, Sertraline can induce transitory changes in serum FSH of male rats without concomitant spermatogenic changes within the testes. This hormonal change appears to be reversible following withholding of Sertraline. The long-term effect of Sertraline usage on hormonal status and spermatogenesis in rats needs further investigation.